Senegal : Financial System Stability Assessment Update. (IMF Staff Country Reports; Country Report ;, 2005)
This Financial System Stability Assessment Update on Senegal reports that the banking sector remains the cornerstone of the financial sector, and risk concentration remains the main source of vulnerability. The largest microfinance institutions (MFI) are sound, but smaller ones are weaker and need to be consolidated and better supervised. Commercial banks and large MFIs provide credit to small- and medium-sized enterprises, but their access to financial services suffers from asymmetries of information and flaws in the judicial system. The development of the regional capital market has not met expectations.